Acute Stroke Management During the COVID-19 Pandemic: Does Confinement Impact Eligibility for Endovascular Therapy?. Issue 8 (August 2020) - Hajdu, Steven D.; Pittet, Valerie; Puccinelli, Francesco; Ben Hassen, Wagih; Ben Maacha, Malek; Blanc, Raphaël; Bracco, Sandra; Broocks, Gabriel; Bartolini, Bruno; Casseri, Tommaso; Clarençon, Frederic; Naggara, Olivier; et al.
Abstract : During the coronavirus disease 2019 (COVID-19) pandemic, the World Health Organization recommended measures to mitigate the outbreak such as social distancing and confinement. Since these measures have been put in place, anecdotal reports describe a decrease in the number of endovascular therapy (EVT) treatments for acute ischemic stroke due to large vessel occlusion. The purpose of our study was to determine the effect on EVT for patients with acute ischemic stroke during the COVID-19 confinement. In this retrospective, observational study, data were collected from November 1, 2019, to April 15, 2020, at 17 stroke centers in countries where confinement measures have been in place since March 2020 for the COVID-19 pandemic (Switzerland, Italy, France, Spain, Portugal, Germany, Canada, and United States). This study included 1600 patients treated by EVT for acute ischemic stroke. Date of EVT and symptom onset-to-groin puncture time were collected. Mean number of EVTs performed per hospital per 2-week interval and mean stroke onset-to-groin puncture time were calculated before confinement measures and after confinement measures. Distributions (non-normal) between the 2 groups (before COVID-19 confinement versus after COVID-19 confinement) were compared using 2-sample Wilcoxon rank-sum test. The results show a significant decrease in mean number of EVTs performed per hospital per 2-week interval between before COVID-19 confinement (9.0 [95% CI, 7.8–10.1]) and after COVID-19 confinement (6.1 [95% CI, 4.5–7.7]), ( P <0.001). In addition, there is a significant increase in mean stroke onset-to-groin puncture time ( P <0.001), between before COVID-19 confinement (300.3 minutes [95% CI, 285.3–315.4]) and after COVID-19 confinement (354.5 minutes [95% CI, 316.2–392.7]). Our preliminary analysis indicates a 32% reduction in EVT procedures and an estimated 54-minute increase in symptom onset-to-groin puncture time after confinement measures for COVID-19 pandemic were put into place.